The Impact of COVID-19 on Orthopedic Surgery Fellowship Training: A Survey of Fellowship Program Directors. Issue 1 (February 2022) - Heaps, Braiden M.; Dugas, Jeffrey R.; Limpisvasti, Orr
Background : The COVID-19 pandemic has had a wide-reaching impact. Graduate medical education of orthopedic surgeons was not spared from the jarring changes. Purpose : We sought to survey fellowship program directors in the field of orthopedic surgery about how the COVID-19 pandemic affected the education of the 2019 to 2020 and 2020 to 2021 fellowship classes and the future of their programs. Methods : In October 2020, an 18-item survey was distributed by an official of the American Academy of Orthopedic Surgeons (AAOS) to the specialty societies that govern fellowship training. Each specialty society then distributed the survey to its respective program directors. A reminder email was sent during the enrollment period. Each respondent was able to complete the survey once. Survey questions were grouped into 3 sections: general information about the fellowship training programs, the impact of COVID-19 on the 2019 to 2020 fellowship class, and the future impact of COVID-19 on the fellowship training programs. Results : Of the 564 accredited orthopedic surgery fellowship programs in the United States, 190 directors responded. Of these, 73.59% reported COVID-19 had a negative impact on the 2019 to 2020 fellowship class. A normal distribution of responses was found regarding didactic and academic learning, research, and mentorship opportunities. A majority of respondents said they believe that there will be no negative impact on patient care the fellows provide in the years to come. Conclusion : Orthopedic surgery fellowship program directors acknowledged that while there were negative effects to training in the pandemic, they did not think these would negatively affect patient care provided by 2019 to 2020 fellows in the short and medium term. They also reported positive outcomes from the experience of the pandemic, including new ways to educate fellows.